The Semantic Revolution - Bengtson, Jason A. (My University, 2015)
Semantic technologies are in the process of revolutionizing the way we store, access, and communicate digital information. It is vital that information professionals be conversant in the foundational concepts upon which these technologies are based. This article uses two implementations of semantic technologies, the semantic web and the Semantic MEDLINE project, to introduce the key ideas of semantic technologies to readers.
Citation: Bengtson, Jason. "The Semantic Revolution." Journal of Electronic Resources in Medical Libraries 15.1 (2015) : 72-82. Print.
Keywords: Semantic Web; Semantic Technology; Summarization Theory; Graph Theory; Triplestore; Semantic MEDLINE